Henry IV and the towns : the pursuit of legitimacy in French urban society, 1589-1610 - Finley-Croswhite, S. Annette (Cambridge studies in early modern history., 1999)
"This book is the first serious study of Henry IV's relationship with the towns of France and offers an in-depth analysis of a crucial aspect of his craft of kingship. Set in the context of the later Wars of Religion, it examines Henry's achievement in reforging an alliance with the towns by comparing his relationship with Catholic League, royalist and Protestant towns."--Jacket